Sintering effect on borosilicate glass-bovine hydroxyapatite composites - (:unkn) unknown (SPRINGER, 2019)
Natural bioceramic resources bring alternative route in hard tissue implant applications; using natural bovine hydroxyapatite (BHA) in these applications provides a more economical and time-friendly approach to these methods. BHA particles were doped (< 100 mu m) with the amount of 5 and 10 wt.% of borosilicate glass (BSG) particles (< 100 mu m). Powder mix pressed to pellets with a cold press machine. Then, green composites were sintered at different temperatures (1000, 1100, 1200, and 1300 degrees C). Highest Vickers hardness was obtained as 232.95 HV and highest compression strength was measured as 117.17 MPa, which is similar to cortical bone. In this study, BSG and BHA composites were produced as a potential implant material for bone engineering applications. Natural hydroxyapatite and recycled borosilicate glasses were used as converting natural sources to biomaterial which is useful and novel.
Keywords: Composites; Bovine bone hydroxyapatite (BHA); Borosilicate glass (BSG); Bioceramic; BONE-DERIVED HYDROXYAPATITE